2018
DOI: 10.1016/j.celrep.2018.09.047
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Multi-omic Analysis of Esthesioneuroblastomas Identifies Two Subgroups Linked to Cell Ontogeny

Abstract: Highlights d Integrative analysis of ENBs identifies neural-like and basallike subgroups d Approximately 35% of basal-like ENBs display IDH2 R172 hotspot mutations d ENBs with IDH2 mutations display a CpG island methylator phenotype (E-CIMP) d Basal-like ENBs display higher intratumoral-infiltrating lymphocytes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
82
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 32 publications
3
82
1
Order By: Relevance
“…A recent study found that half of ENBs have clinically relevant genomic alteration, which are identified in different genes such as TP53 , PIK3CA , NF1 , CDKN2A , or CDKN2C . Recently, Classe et al reported an integrative multiomics analysis of ENB identifying two subgroups of ENBs: neural and basal . They showed that the basal‐like subgroup includes poorly differentiated tumors with a high expression of embryonic genes and a shorter survival for patients sharing some similarities with our cohort of pediatric ENBs (poor survival, dedifferentiated tumor, high Ki67).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A recent study found that half of ENBs have clinically relevant genomic alteration, which are identified in different genes such as TP53 , PIK3CA , NF1 , CDKN2A , or CDKN2C . Recently, Classe et al reported an integrative multiomics analysis of ENB identifying two subgroups of ENBs: neural and basal . They showed that the basal‐like subgroup includes poorly differentiated tumors with a high expression of embryonic genes and a shorter survival for patients sharing some similarities with our cohort of pediatric ENBs (poor survival, dedifferentiated tumor, high Ki67).…”
Section: Discussionsupporting
confidence: 78%
“…They showed that the basal‐like subgroup includes poorly differentiated tumors with a high expression of embryonic genes and a shorter survival for patients sharing some similarities with our cohort of pediatric ENBs (poor survival, dedifferentiated tumor, high Ki67). Interestingly, basal‐like ENBs harbor IDH2 mutations in one‐third of cases that might represent a therapeutic option …”
Section: Discussionmentioning
confidence: 99%
“…reported different mutational profiles in low‐grade and high‐grade ONBs, with no recurrent mutations in low‐grade ONBs, and IDH2 and TP53 mutations in higher‐grade ONBs. TP53 mutations have also been reported by others in high grade ONBs . It is possible that high‐grade tumours have a higher mutational load than low‐grade tumours, or have mutations that are more immunogenic.…”
Section: Discussionmentioning
confidence: 55%
“…This might be due to the stronger immunogenic profile of high‐grade tumours. The mutational landscape of ONBs is still poorly known . Classe et al .…”
Section: Discussionmentioning
confidence: 99%
“…This enabled researchers to identify molecular relationships between cancers, cluster prognostic variants and elucidate future therapeutic targets to explore. Furthermore, much of this anonymised data is publicly available on the Genomic Data Commons Data Portal for future research projects to utilise [146], and three non-TCGA cancer studies included in this review reported using this public data to overcome the rarity of their studied cancer type, to confirm cell ontology and even simply as a comparative control for their own gene expression data [69,70,99]. An additional point of interest was the computational algorithms used to overcome the statistical challenge of data integration in multi-omic studies of rare disease.…”
Section: Discussionmentioning
confidence: 99%